How the availability of anti-C5a agents could change the management of ANCA-associated Vasculitis - Dario Roccatello; Roberta Fenoglio; Valentina Oddone; Savino Sciascia (Karger Publishers, 2022)
Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a cluster of potentially life-threatening disorders often involving the kidney with a necrotizing crescentic glomerulonephritis with scanty deposition of immunoglobulins and complement. Historically the role of complement has been considered ancillary. Recently, an anti-myeloperoxidase (MPO) AAV model in complement-deficient mice has shown an involvement for the complement cascade in the development of the renal injuries. Further animal studies showing that in contrast to mice deficient for factor B and C5 animals deficient for C4 were susceptible to AAV development by injection of anti-MPO antibodies emphasized the specific involvement of the alternative pathway. Consonantly, the C5a receptor (Cd88) blockade was found to protect mice from MPO AAV. CCX168, i.e., Avacopan, a powerful inhibitor of C5a receptor that can be administered orally, was shown to reduce the pro-inflammatory effects of C5a and abolish the activation of neutrophils, their migration and adherence to endothelium, and the vascular endothelial cell retraction that increases permeability. Summary: Avacopan was found to be safe in healthy volunteers given a wide range of doses in a Phase 1 clinical trial. The Phase 2 trial CLEAR assessed the possibility to decrease dose or entirely replace glucocorticosteroids in the Standard of Care (SoC) therapy of AAV. Avacopan, added to CYC or RTX either in combination with GCs or not, shortened the time to remission in patients with either newly diagnosed or relapsing AAV. The Phase 3 ADVOCATE study compared the ability of an Avacopan-associated regimen to induce and sustain remission in AAV patients vs a conventional GC-associated scheme. Remission at week 26 was observed in 72.3% of patients given Avacopan and in 70.1% of those given prednisone. Sustained remission at week 52 (second primary endpoint) was obtained in 65.7% of patients given Avacopan and in 54.9% receiving prednisone. The Avacopan-associated regimen was non-inferior at week 26, and superior at week 52 in sustaining remission as compared to the GC-based scheme. Key point: The results of the ADVOCATE trial opened new prospects for the treatment of AAV and also other immune-mediated diseases with renal involvement. The possible position of Avacopan in a routinary clinical setting and its possible indications in specific subsets of patients with AAV are extensively discussed.